Simpler component of non-hydrostatic UNBabc mapping function using nonlinear curve fitting method - Sakidin, H. (American Institute of Physics Inc., 2016)
UNBabc mapping function for wet component needs 11 operations to be carried out in order to obtain the mapping function value. This wet component is provided in a form of continued fraction. To obtain faster result faster calculation is required. Therefore, there is a need to simplify the mapping function models. In this paper the method used to simplify non hydrostatic UNBabc mapping function model is nonlinear curve fitting method. This model has been selected to be simplified, due to its ability to achieve mapping function value, down to 2 degree of elevation angle. To show that the simplified model result approach the original model the sum of error are used. The comparison between the original models with the simplified models can be shown by calculating the sum of error. The number of mathematical operation can be reduced from 11 operations to 2 operations after the process of simplification of the model. Â© 2016 Author(s).